2012
DOI: 10.1159/000334845
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Atrophy of the Medial Temporal Areas and Cognitive Functions in Elderly Adults with Mild Cognitive Impairment

Abstract: Aim: The current study sought to determine which types of cognitive function are related to atrophy of the bilateral medial temporal areas including the entorhinal cortex (MTA-ERC) in elderly adults. Methods: The subjects were 96 elderly adults (mean age 75.3 years) with mild cognitive impairment. Subjects underwent Wechsler Memory Scale-Revised, logical memory I and II (WMS-R, LM I and II), Rey complex figure retention tests after 3 and 30 min (RCF-3 min and RCF-30 min), digit span backword (DSB), digit symbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 135 publications
1
7
0
Order By: Relevance
“…Similar results were observed in several earlier studies in healthy older adults [4854] and older adults with MCI [5457]. Nevertheless, other studies in healthy older adults observed associations between aerobic fitness and aspects of executive function [52], memory [49] and between dynamic balance and general cognitive function [48], or executive function [48, 58].…”
Section: Discussionsupporting
confidence: 89%
“…Similar results were observed in several earlier studies in healthy older adults [4854] and older adults with MCI [5457]. Nevertheless, other studies in healthy older adults observed associations between aerobic fitness and aspects of executive function [52], memory [49] and between dynamic balance and general cognitive function [48], or executive function [48, 58].…”
Section: Discussionsupporting
confidence: 89%
“…According to the findings of Silveri et al (2007), lower scores on selective attention tasks in patients with MCI predict the development of dementia later in life. Similarly, Shimada et al (2012) have found attention tasks to be useful predictors of atrophy in the medial temporal lobe and entorhinal cortex. Some studies have even proposed a so-called anatomo-functional syndrome in AD, hypothesizing that deficits in attention may lead to memory problems, corroborating the notion of a common deficient mechanism in MCI (Silveri et al, 2007).…”
Section: Discussionmentioning
confidence: 86%
“…The process of consolidation is mediated by the medial temporal cortex, an area known to be negatively affected early in AD (Kramer & Miller, 2000) and aMCI (Dudai, 2004; Manes et al, 2008; Masdeu, Zubieta, & Arbizu, 2005; Squire & Alvarez, 1995). Atrophy within the medial temporal lobe (with entorhinal cortex) in MCI is associated with rapid forgetting (within 30 minutes) of a learned story (Shimada et al, 2012). How long the medial temporal lobe remains involved in the memory consolidation and retrieval process remains a point of debate.…”
Section: Discussionmentioning
confidence: 99%